Systematic review of crisis reactions toward major disease outbreaks: application of the triple helix model in the context of tourism. Issue 2 (3rd September 2021) - Chen, Li-Hsin; Munoz, Kyrie Eleison; Aye, Nandar
Abstract : Purpose: While academia, industry and government have made various efforts to ameliorate the impacts of Covid-19, no study has hitherto used an integrative framework to assess the reactions of all three of these sectors to previous multinational epidemics. Such fragmentation ignores the holistic nature of crisis management. To better understand the impacts of health crises on tourism, this study aims to examine the past literature related to academic, industrial and governmental responses to multinational epidemics through the lens of the triple helix model. Design/methodology/approach: Based on preferred reporting items for systematic reviews and meta-analyzes and the best-fit approach, this paper conducts a systematic review of the literature published between 2000 and 2020 on five multinational epidemics that had significant impacts on the tourism industry: food and mouth disease, severe acute respiratory syndrome, bird flu (novel influenza A and avian flu), Ebola and middle east respiratory syndrome. Thematic analysis was used to identify major themes in the 63 relevant articles identified. Findings: No substantial increase was found in the quantity of multinational epidemic-related studies after 2010. Collectively, the 10 identified themes strongly emphasized economic recovery. Originality/value: No existing tourism-related study examines reactions toward multiple health crises by integrating three important sectors: academia, industry and government. This study fills that research gap with a systematic review of past multinational epidemics and proposes an integrative framework. It also provides recommendations for future research and health-crisis management practices.